Genetic Diversity Analysis of Sambar Deer (Cervus unicolor) Based on Mitochondrial DNA D-loop Sequence - Jofaturrahmah, Aisyah; Fanani, Anhar Faisal; Wibowo, Ari; Indana, Khoiru; Putra, Widya Pintaka Bayu; Suhardi, Suhardi (Jurnal Sain Peternakan Indonesia, 2025)
This study aimed to analyze the genetic diversity of the sambar deer (Cervus unicolor) population through mitochondrial D-loop DNA sequencing. The findings provide valuable insights into the conservation status of this vulnerable species in the region and inform future management strategies for Cervus unicolor. Blood samples from 10 individual sambar deer, consisting of 8 females and two male deer, were amplified using PCR and then sequenced. Data analysis of the genetic diversity of sambar deer was carried out using the genome sequencing method from NCBI, Bioedit 7.7.1 software, DNAsp 5.1, and MEGA 11 Software. The results of this study were that the DNA concentration test in sambar deer had an average of 12.375 ng/uL, with an average DNA purity test = 1.34, with 10 samples divided into 3 haplotypes. The level of genetic diversity of sambar deer from all samples is π = 0.01745 ± 0.00380, and haplotype diversity of Hd = 1,000 ± 0.045. Based on the phylogenetic tree, there are two parts: the Asian and Kalimantan regions. The conclusion of the current study showed that sequencing analysis of Sambar deer shows relatively high diversity and is a reasonable basis for performance selection and development of modern Sambar deer breeding.